(3QSGdI aj GdLHQ hGdebGHdIs - (3eMeO Hf eMeO GdfSajs
(3ChdgG (B:s
(3hHYO abO EdJeS efi HYV CUMGHi Cf CMQQ ef GdbhGYO GddGReI eYQaJgG ai Yde GdLHQ hGdebGHdI s
(3BNQgG (B:s
(3GdSWhM hGdNWhW aPdc jYQa HEYJHGQgG eG YQaJg ef bHd hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HgG Jedc HGSe CMeO Hf Ydi GdQMjHGfi GdMfHdi SfI (B1145 (3g`s
(3eUOQ GbJfGA GdCUd (B:s
(3eOQSI GdMLjGJ (B_ (3GdehUd (B(61) s
Keywords: (3GdeLGejYs